1999
DOI: 10.1074/jbc.274.26.18503
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A Modifications Characteristic of Salmonella typhimurium Are Induced by NH4VO3 inEscherichia coli K12

Abstract: Two-thirds of the lipid A in wild-type-component regulatory system, and also occurred in E. coli msbB or htrB mutants. The lipid A variants that accumulate in NH 4 VO 3 -treated E. coli K12 are the same as many of those normally found in untreated Salmonella typhimurium and Salmonella minnesota, demonstrating that E. coli K12 has latent enzyme systems for synthesizing these important derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
392
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(396 citation statements)
references
References 55 publications
(101 reference statements)
3
392
1
Order By: Relevance
“…In E. coli K-12, approximately two-thirds of the lipid A is a hexa-acylated disaccharide of glucosamine with monophosphate groups at positions 1 and 49 (1-O-P lipid A). The remainder contains a diphosphate moiety at position 1 (1-O-PP lipid A) (Zhou et al, 1999). A small amount of 1-dephosphorylated lipid A (identified herein as 1-OH) can be generated during the mild acid hydrolysis procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In E. coli K-12, approximately two-thirds of the lipid A is a hexa-acylated disaccharide of glucosamine with monophosphate groups at positions 1 and 49 (1-O-P lipid A). The remainder contains a diphosphate moiety at position 1 (1-O-PP lipid A) (Zhou et al, 1999). A small amount of 1-dephosphorylated lipid A (identified herein as 1-OH) can be generated during the mild acid hydrolysis procedure.…”
Section: Methodsmentioning
confidence: 99%
“…two-thirds of the lipid A is a hexa-acylated disaccharide of glucosamine in which monophosphate groups are attached at positions 1 and 49 (1-O-P lipid A) (Zhou et al, 1999). The remaining one-third of lipid A contains a diphosphate moiety at position 1 (1-O-PP lipid A, Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these gene products except pmrM are essential for the biosynthesis of Ara4N-lipid A and for resistance to CAMPs (18). In vitro studies by Raetz and co-workers have shown a pathway for the biosynthesis of UDP-L-Ara4N from UDP-glucose (UDP-Glc) (19)(20)(21). The pathway begins with the oxidation of UDP-Glc to UDP-glucuronic acid (UDP-GlcA) catalyzed by the well-characterized UDP-Glc dehydrogenase (PmrE/Ugd) ( Figure 1).…”
mentioning
confidence: 99%
“…UDP-GlcA is then oxidatively decarboxylated by ArnA (PmrI) to yield UDP-4-keto-arabinose (UDPAra4O), which in turn is transaminated to produce UDP-4-amino-arabinose (UDP-Ara4N) in a reaction catalyzed by ArnB (PmrH). On the basis of sequence similarity to enzymes with known activities, additional gene products of the pmrHFIJKLM operon have been proposed to catalyze the transfer of Ara4N from the UDP intermediate to lipid A (19,(21)(22)(23)(24). The enzymes in this pathway are potential targets for antibacterial drug design.…”
mentioning
confidence: 99%